APPLICATION OF THE BENCHMARKING TOOL IN OPERATIONAL PERFORMANCE - Rodrigues, Camila Ariele (Revista Interface Tecnológica, 2023)
Benchmarking is a management tool that allows comparing and evaluating the performance of a company in relation to its competitors or other reference organizations in its sector. This study aims to explore the application of benchmarking in the analysis of operational performance in inventory management. When applied to operational performance, the tool can help identify opportunities for improving processes, reducing costs and increasing efficiency. By using the benchmarking tool, companies can access relevant information about innovative and effective practices used by other organizations, being able to implement them in their own management. The article discusses how the tool can be used to improve operational performance, the benefits of the tool to drive organizational change and continuous improvement. For this, bibliographic research and case studies were carried out, where the best practices used by leading companies were identified, thus encouraging the company to adopt this technique as part of its continuous efforts to increase its competitiveness and achieve success.
Keywords: Benchmarking; Competitiveness; Companies; Management; Performance